2013
DOI: 10.1017/s1368980013002656
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with not using folic acid supplements preconceptionally

Abstract: Objective: Neural tube defects are among the most common birth defects worldwide. Folic acid intake from one month before to three months after conception reduces the likelihood of neural tube defects by at least 50 %. Since 1995, several campaigns have been organised in the Netherlands which resulted in 51 % of pregnant women using folic acid supplements during the entire recommended period in the northern part of the Netherlands in 2005. Our research question was to gain insight into the current prevalence a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
21
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 28 publications
4
21
1
Order By: Relevance
“…(2224) It indicated that health education should be strengthened, specially making more efforts on prepregnancy education and cooperating with public media. Agreement with other studies, (23,25) the ones with higher education levels, income, multiparous and age were more likely to take folic acid before pregnancy. Therefore, preconceptional health education should take more concern on the pregnant women with lower education levels, income and nulliparous.…”
Section: Discussionsupporting
confidence: 87%
“…(2224) It indicated that health education should be strengthened, specially making more efforts on prepregnancy education and cooperating with public media. Agreement with other studies, (23,25) the ones with higher education levels, income, multiparous and age were more likely to take folic acid before pregnancy. Therefore, preconceptional health education should take more concern on the pregnant women with lower education levels, income and nulliparous.…”
Section: Discussionsupporting
confidence: 87%
“…Riazi reported that although 80% of women had planned pregnancies, only 9% used folic acid in the preconception period (18). In the Mannien et al's study, 55.5% of women used folic acid in the preconception period (27). In the present study, 48% of women who attended a PCC clinic routinely used folic acid supplements, while this rate was 20% in women who did not attend the clinic before pregnancy.…”
Section: Discussioncontrasting
confidence: 42%
“…Both folic acid utilisation and passive smoking may act as proxy indicators for a less healthy lifestyle. 24,25 Inadequate health care utilisation can also be an expression of a less healthy lifestyle or less health consciousness. 24 However, we were not able to test this hypothesis, and thus it requires further research.…”
Section: Discussionmentioning
confidence: 99%